2014
DOI: 10.1177/2158244014529779
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Impediments for Elective Music and Sport in Adolescent Males

Abstract: Within the culture of an all-male private school, sport often holds a special status as compared with music. As an area of learning and participation, sport is typically associated with masculinity and receives broad social acceptance, whereas music is often seen at the margins of the curriculum and considered as an activity for a select few who are innately talented. Because of these perceptions, participation rates for males are often higher for sport than they are for music. With this as our context, this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…Why this should still be the case given the impetus towards more gender equality in the developed world is puzzling. It may be that boys tend to be more interested in other activities, for instance sports (Waters, McPherson, & Schubert, 2014). There may also be insufficient role models that challenge gender stereotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Why this should still be the case given the impetus towards more gender equality in the developed world is puzzling. It may be that boys tend to be more interested in other activities, for instance sports (Waters, McPherson, & Schubert, 2014). There may also be insufficient role models that challenge gender stereotypes.…”
Section: Discussionmentioning
confidence: 99%
“…They may also come under greater pressure to conform to gender stereotypes, avoiding any activity that might be viewed as feminine (Hallam et al, 2008). Sport as a hobby may become more attractive than music (Waters et al, 2014). Furthermore, the curriculum for instrumental lessons may not offer them sufficient choice in relation to their need to define their developing masculinity, leading to a loss of motivation (Varvarigou, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Given that value is theorized to predict academic choices, it appears that the overall low valuing of music may lead to students turning away from music and choosing other subjects at school. In the context of a boys' high school, Waters et al (2014) found that when students did not enjoy music or find it interesting, their interest in selecting it as an elective subject was impeded. Simpkins et al (2010) found that the strongest predictor of children's choices of subjects in high school was their valuing of the subject.…”
Section: Value As Predictor Of Elective Subject Choicementioning
confidence: 99%
“…The Irish education system is influenced by competitive individualistic values (Lynch, 1987;O'Flaherty & Gleeson, 2014, an ideology which is reflected in the assessment-driven nature of the LC and the points system. Waters, McPherson, and Schubert (2014) argue that there is limited research regarding the factors that influence subject choice during second-level education, which is surprising considering the profound effect of subject selection on the future careers of adolescents.…”
Section: Some Relevant Irish Contextmentioning
confidence: 99%
“…Equally, students identified that if they had not taken the subject in lower second level, they were less likely to select it for LC. Further research suggests that future education or career aspirations are a factor which affects student attitudes towards subject selection (Millar, Kelly, & NCCA, 1999;Waters et al, 2014). Lamont and Maton (2008) consider a combination of factors which 'may shape pupils' decisions about music: 'how difficult they think the subject is, how good they think they may be at it, and how important it is are all potentially powerful influences' (p. 269).…”
Section: Second-level Music Educationmentioning
confidence: 99%